MAKE-UP KIT PACKAGE DESIGN FOR ACTIVE WOMAN - Risdiyono Risdiyono (Faculty of Industrial Technology Universitas Islam Indonesia, 2013)
Packaging has a very big role in the success of product. Not only as product’s protector or as container, packaging plays critical and essential function of building brand and adding emotional value. Packaging can also represent a significant portion of a product’s selling price. Packaging cost for luxury goods such as perfume and cosmetics is accounted approximately for 30% and even maybe as high as 40% of a product’s selling price. This paper discusses a comprehensive overview of making a make-up kit package design starting from market analyses to concept generation and prototyping. It is aimed at designing a fashionable, convenience, and environment friendly make-up kit package for active women. Three cosmetic products i.e. facial powder, lipstick and facial blotter are selected to be combined in the kit since they are the most important products needed by active women in a busy time. The shape of tray has been improved to reduce the waste of powder in the edge corner of the tray. Since the kit is made from leather, it is highly possible that it can reduce the occurrence of breaking compact powder when the case accidently felt down. The product is also environment friendly since it is refillable. With these entire new features, it is quite confident to say that this product seems to be better compared to the existing products in term of convenience, compact and fashionable.